2022
DOI: 10.1177/2277436x211073849
|View full text |Cite
|
Sign up to set email alerts
|

Struggling with Primary Infertility: Psychological Well-Being and Associated Factors in North Indian Women

Abstract: The study aimed to understand the effect of primary infertility on the psychological well-being of women. In addition, the study has assessed the impact of socio-demographic variables, reproductive trajectories and lifestyle variables on psychological well-being independently and in light of their dynamic interaction among North Indian women. This study was conducted among 250 infertile women with primary infertility attending the Gynaecology OPD and 250 age-matched fertile women from Delhi. Pretested quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…The majority of women had moderate wellbeing levels, while a significant portion of women had high well-being levels. The results of the study are in line with the study carried out by Sharma et al (2022) which revealed that infertility was the major stressor among infertile women which disturbed their wellbeing and also mentioned that mental well-being was often ignored while treating infertility, so proper counselling must be provided to ensure a healthy pregnancy. In India, it is customary for married couples to have children within the first year of their marriage to avoid societal pressure, stigma, and discrimination.…”
Section: Level Of Well-being Among Infertile Womensupporting
confidence: 82%
“…The majority of women had moderate wellbeing levels, while a significant portion of women had high well-being levels. The results of the study are in line with the study carried out by Sharma et al (2022) which revealed that infertility was the major stressor among infertile women which disturbed their wellbeing and also mentioned that mental well-being was often ignored while treating infertility, so proper counselling must be provided to ensure a healthy pregnancy. In India, it is customary for married couples to have children within the first year of their marriage to avoid societal pressure, stigma, and discrimination.…”
Section: Level Of Well-being Among Infertile Womensupporting
confidence: 82%
“…But there were statistically highly significant differences (P≤0.01) between primary and secondary type of infertility in younger women group, but only significant differences (P≤0.05) in older women between the two types of infertility were studied group. About two percent of infertile women have primary infertility [28]. Primary infertility among women was more common than secondary infertility [29].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it decreased obesity, diabetes, and infertility rate [ 17 ]. The effective factors on the well-being and health of women with primary infertility were investigated in India and factors, such as psychological problems, duration of infertility, insufficient physical activity, education level, sleeping pattern, and family structure were shown to be crucially important in infertility [ 18 ]. The study by Palomba on 216 women under the treatment by IVF/ICSI revealed that regular physical activity before fertilization procedure improves fertility outcomes in infertile obese women [ 19 ].…”
Section: Introductionmentioning
confidence: 99%